An Act to prevent and punish the sale of Arms and Ammunitions to Indians, Sec. 1., in The Compiled Laws of the Territory of Arizona 99 (John P. Hoyt ed., 1877). - (:unkn) unknown (General Publisher, 1877)
Any person or persons within this Territory who shall sell or give arms or ammunition to any Indians, or repair arms for them, shall, upon conviction thereof, be punished as follows .
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES